2016
DOI: 10.1111/anti.12274
|View full text |Cite
|
Sign up to set email alerts
|

Emancipatory or Neoliberal Food Politics? Exploring the “Politics of Collectivity” of Buying Groups in the Search for Egalitarian Food Democracies

Abstract: In the context of apolitical tendencies in food studies, this paper explores how alternative food networks can contribute to developing emancipatory food politics rather than constitute a tool to reproduce neoliberal subjectivities. For this purpose, I contend that the post-political literature offers a useful approach to examining the concept of food politics by developing a more robust theoretical framework, permitting the establishment of linkages with broader contemporary processes of social change. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 58 publications
0
41
0
7
Order By: Relevance
“…En estos casos puede observarse la premisa de reconexión propia de las RAA, definida por Dowler et al, citados por Bos et al (24), como la reunión de todos los elementos de los sistemas alimentarios, la cual se fortalece, entre otras, por las estrategias que procuran el establecimiento de relaciones entre todos los actores de la cadena mediante espacios presenciales y virtuales. Sin embargo, mientras estas relaciones en otros estudios se documentan fortalecidas entre produc-tores y consumidores (9) y, de hecho, muchas de las experiencias son propiciadas por estos últimos (26)(27)(28), entre los casos estudiados el fomento de la reconexión, relocalización y reintegración del sistema alimentario está siendo promovido por los productores que actúan como distribuidores directos o por entidades o personas que se dedican a la distribución de alimentos provenientes de producción orgánica y local. Por su parte, en los consumidores hay un aprovechamiento más de orden individual de estas RAA.…”
Section: Discussionunclassified
“…En estos casos puede observarse la premisa de reconexión propia de las RAA, definida por Dowler et al, citados por Bos et al (24), como la reunión de todos los elementos de los sistemas alimentarios, la cual se fortalece, entre otras, por las estrategias que procuran el establecimiento de relaciones entre todos los actores de la cadena mediante espacios presenciales y virtuales. Sin embargo, mientras estas relaciones en otros estudios se documentan fortalecidas entre produc-tores y consumidores (9) y, de hecho, muchas de las experiencias son propiciadas por estos últimos (26)(27)(28), entre los casos estudiados el fomento de la reconexión, relocalización y reintegración del sistema alimentario está siendo promovido por los productores que actúan como distribuidores directos o por entidades o personas que se dedican a la distribución de alimentos provenientes de producción orgánica y local. Por su parte, en los consumidores hay un aprovechamiento más de orden individual de estas RAA.…”
Section: Discussionunclassified
“…However, according to recent comprehensive reviews on the field(see Tregear 2011and Goodman et al,(2012)), an important part of this work has been developed in a conceptual vacuum and/or fuzziness, often adopting a rather un-critical and ideographic approach to study the phenomenon.Of particular interest was Goodman's (2004a) intervention stressing the need to reassess claims made by much of the European literature on whether AFNs represent a paradigm shift, that is, if they represent a change in social structures and power relations. In this line, using political economy and political ecology frameworks, critical scholars have argued that not only the 'local' but other attributes of AFNs such as fair trade schemes or environmentally friendly certifications might actually contribute to capitalist development, exclusion of vulnerable farmers and low-income consumers, and labour exploitation (Goodman, 2004b;Guthman, 2004).Motivated by these critical perspectives, scholars have exposed how in many cases these 'ethical' and 'sustainable' initiatives can conceal potential environmental impacts and reproduce social inequalities, and might also be fostering an infertile consumer politics by deepening individualist practices and reproducing neoliberal configurations that hinder social change (Moragues-Faus, 2017b). Nevertheless, other political ecologists claim that AFNs aim to de-commodify food and agriculture (Pimbert et al, 2001).…”
Section: A) Critique Through a Historical And Multi-scalar Analysis Omentioning
confidence: 99%
“…A telling example is the marginalization of self-provision practices compliant with sustainability principles in the food literature in favor of market-based alternative food systems, as illustrated by Jehlička and Smith(2011) in the case of the Chez republic. Recent contributions are exploring how these connections might take shape contributing to the development of transformative social movements mainly under the food sovereignty umbrella (see special issues in Third World Quarterly vol 36 and Globalizations vol 12) and fostering egalitarian and emancipatory food politics (Moragues-Faus, 2017b).…”
Section: C) Problematising the Production Of Knowledge And Creating Nmentioning
confidence: 99%
“…For example, participants in Valencia's buying groups show a commitment to promote social change through the act of buying food. A Participatory Action Research 2012-2013 study (Utópika & ISF, internal report) concluded that buying groups in the city of Valencia had a common socio-political project that coalesced around the struggle for food sovereignty (see Moragues-Faus, 2017a). This broader political project also included specific criteria to select products and producers, such as organic, local and seasonal.…”
Section: Stabilitymentioning
confidence: 99%
“…Although AFNs resist a consensual definition, they are generally characterised by: (1) short distances between producers and consumers; (2) small farm size and scale and organic or holistic farming methods; (3) the existence of food purchasing avenues such as food cooperatives, farmers markets and community supported agriculture; and (4) a commitment to the social, economic and environmental dimensions of sustainable food production, distribution and consumption (Jarosz, 2007). However, critical scholars have warned about an idealization of AFNs, since in many cases they can mask potential environmental impacts and reproduce social inequalities (Moragues-Faus & Marsden 2017), for example by creating exclusive landscapes for highly educated and well-off consumers, or concealing exploitative labour conditions (Goodman, 2004;Guthman, 2004;Moragues-Faus, 2017a). Since the 2008-2009 financial and food crisis, scholars have progressively moved from a celebratory analysis of AFNs -in terms of their environmental, social and economic contribution to sustainable development goals -to develop more critical accounts of these initiatives (Moragues-Faus and Marsden, 2017).…”
Section: Introductionmentioning
confidence: 99%